Gerbang Pembayaran Nasional (GPN) Sebagai Instrumen Dalam Optimalisasi Penarikan Pajak Penghasilan (PPh) Pada Transaksi E-Commerce - Immanuel Riyadi Tampubolon; U Sudjana; Amelia Cahyadini (Kyadiren, 2020)
Information Communication and Technology (ICT) has changed the form of traditional business to a digital-based business known as e-commerce. The development of e-commerce in Indonesia increases in size every year and affects the tax reception especially on the matter of income tax. The self-assessment system is a form of tax collection that emphasizes in recording, paying, and reporting incomes directly to businessmen. This causes many businessmen are considered not doing their tax liability. The National Payment Gateway (NPG) is an instrument that can record the incomes of businessmen for the benefit of income tax collection optimizations. However, there are currently no laws that specifically regulate records of businessmen incomes through NPG. This research is a descriptive analysis with the use of normative and empirical juridical approach. The results of the study indicate that the concept of withdrawing income tax (PPh) through the National Payment Gateway Instrument (GPN) requires a strong and concrete legal basis that regulates the requirements that must be met as an e-commerce business actor. In addition, it is also necessary to regulate cooperation between related institutions based on the Whole of Government theoretical approach in implementing the concept.